Scientific validation of traditional knowledge on techniques for sorting Myristica spp. seeds practiced by the farming community of Palakkad district, Kerala, India - K A Suresh Kumar; C Anilkumar; K G Ajithkumar; T M Prajith (Journal of Traditional and Folk Practices (JTFP), 2021)
Palakkad is well known for agro biodiversity and agriculture based traditional knowledge. This paper deals with scientific analysis of traditional knowledge related to sorting viable seeds by various rural farming communities in Palakkad district of Kerala state. The present study was undertaken with the objective of documenting traditional knowledge of farmers related to sorting of viable seeds, viz. floating and shaky seeds never sprout. Another important objective was to pave the way for value addition of such traditional knowledge by giving logical and scientific interpretation. The seeds of various Myristica species (Myristicaceae) were considered for the scientific validation of the documented traditional knowledge because the distribution of these endemic and endangered tropical forest trees are restricted to a unique but highly fragile and fragmented fresh water ecosystem called Myristica swamps. The value added and validated traditional knowledge is documented and made available as knowledge repository to sustainable farming as well as community conservancy.